Cardiovascular disease and lung cancer - de Jesus, Mikhail; Chanda, Anindita; Grabauskas, Titas; Kumar, Manish; Kim, Agnes S. (Frontiers in Oncology, 2024)
Lung cancer is the second most common cancer worldwide and the leading cause of cancer-related death. While survival rates have improved with advancements in cancer therapeutics, additional health challenges have surfaced. Cardiovascular disease (CVD) is a leading cause of morbidity and mortality in patients with lung cancer. CVD and lung cancer share many risk factors, such as smoking, hypertension, diabetes, advanced age, and obesity. Optimal management of this patient population requires a full understanding of the potential cardiovascular (CV) complications of lung cancer treatment. This review outlines the common shared risk factors, the spectrum of cardiotoxicities associated with lung cancer therapeutics, and prevention and management of short- and long-term CVD in patients with non-small cell (NSCLC) and small cell (SCLC) lung cancer. Due to the medical complexity of these patients, multidisciplinary collaborative care among oncologists, cardiologists, primary care physicians, and other providers is essential.